Copper-peptides mimicking catalytic activity of laccase in oxidation reactions - Begum, Sharifa Zaithun (2020)
Laccase, an oxidative enzyme naturally found in fungi and bacteria, has been widely used in the fields of chemical and bio-catalysis. Its active site contains several copper ions making it very interesting for studies related to the structure and catalytic mechanisms. However, extracting laccase uses large amounts of organic solvents to attain low yield; making it a less preferred choice for all green chemistry applications. The significance of this study is to mimic and enhance the catalytic activity of the highest oxidation activity reported laccase from Trametes versicolor. The four peptide sequences of the active sites found in most laccases was designed into nona (Np), hepta (Hp), tetrapeptides (Tp1 and Tp2) using computational techniques. The peptides were synthesized using Fmoc SPPS, analyzed and purified using HPLC and LC-MS. Copper(II)-peptides identified as Np-CuC, Np-CuS, Np-CuN, Hp-CuC, Hp-CuS, Hp- CuN, Tp1-CuC, Tp1-CuS, Tp2-CuC and Tp2-CuS were synthesized, crystallized and analyzed using FTIR, Raman, NMR, AAS, XPS and CD. Different molar ratio of peptides to copper(II) ions were analyzed for binding studies. These peptides and copper-peptides were tested for their catalytic activity in oxidation reaction of benzyl alcohol where both oxidation to benzaldehyde and disproportionation to toluene and phenol were achieved simulataneously. Np-CuC was observed to have higher catalytic activity (62.3%, 100% selectivity) than laccase (40.8%, 19.1% selectivity) towards benzaldehyde. They were also used as catalysts in the degradation of twelve pharmaceutical active compounds (PhACs). Tp2-CuS (1:2) proved to be a better catalyst in the degradation of PhACs. Oxidation of 5-ASA and DCA catalyzed by these copper peptides where Hp-CuS provided the highest yield of the oxidized product (46.5%). These activities were compared with laccase (positive control) and no catalyst (negative control). Overall, Np-CuC, Tp2-CuS and Hp-CuS were found to be better catalysts for oxidation reactions compared to their parent peptides and laccase.